Intranasal MSC-derived A1-exosomes ease inflammation, and prevent abnormal neurogenesis and memory dysfunction after status epilepticus - Long, Qianfa (Proc Natl Acad Sci U S A, 2017)
Status epilepticus (SE), a medical emergency that is typically terminated through antiepileptic drug treatment, leads to hippocampus dysfunction typified by neurodegeneration, inflammation, altered neurogenesis, as well as cognitive and memory deficits. Here, we examined the effects of intranasal (IN) administration of extracellular vesicles (EVs) secreted from human bone marrow-derived mesenchymal stem cells (MSCs) on SE-induced adverse changes. The EVs used in this study are referred to as A1-exosomes because of their robust antiinflammatory properties. We subjected young mice to pilocarpine-induced SE for 2 h and then administered A1-exosomes or vehicle IN twice over 24 h. The A1-exosomes reached the hippocampus within 6 h of administration, and animals receiving them exhibited diminished loss of glutamatergic and GABAergic neurons and greatly reduced inflammation in the hippocampus. Moreover, the neuroprotective and antiinflammatory effects of A1-exosomes were coupled with long-term preservation of normal hippocampal neurogenesis and cognitive and memory function, in contrast to waned and abnormal neurogenesis, persistent inflammation, and functional deficits in animals receiving vehicle. These results provide evidence that IN administration of A1-exosomes is efficient for minimizing the adverse effects of SE in the hippocampus and preventing SE-induced cognitive and memory impairments.